Experimental Study on the Influence Mechanism of the Structural Plane to Rockbursts in Deeply Buried Hard Rock Tunnels - Guangtan Cheng; Jian Zhang; Qiang Gao; Chuanxiao Liu (Shock and Vibration)
During the excavation of a large number of deeply buried tunnels and mining projects, rockburst disasters occur frequently due to the complex geologic environment in deep underground, including high initial geostress, adverse tectonic actions, and excavation disturbance. Many rockbursts have been found to be induced by some small-scale structural planes in the area around the tunnels during the construction of Jinping II hydropower station. In order to study the influence mechanisms of the structural plane to rockbursts, the physical simulation tests of rockbursts under biaxial stress conditions are carried out using marble samples by considering different relative positions of the structural plane with tunnels, namely, in tunnel spandrel, in tunnel sidewall, and at the intersection with the tunnel. The digital image correlation (DIC) technique is used to trace the evolution of the deformation on the surface and the rockburst process of the marble sample. The results reveal that three types of rockbursts are identified, namely, fault-slip rockburst, split bulking rockburst, and shear rupture rockburst, and their evolution processes are reproduced. The presence of small-scale structural planes in the vicinity of deep tunnels could be one of the major influence factors in triggering rockbursts. The findings could provide helpful references for predicting the development process and the design of burst-resistant measures for this type of rockbursts.